Penegakkan Hukum terhadap Tindak Pidana Pencurian Data Pribadi melalui Internet Ditinjau dari Undang-Undang Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 tentang ITE (Informasi dan Transaksi Elektronik) - Mia Puspita Sari; Damrah Mamang; Moh Zakky (Jurnal Hukum Jurisdictie, 2021)
Mia Puspita Sari, 1220150021, Law Enforcement of the Crime of Personal Data Theft Through the Internet Judging from Law No. 11 of 2008 concerning Amendments to Law No.19 of 2016 concerning ITE (Information and Electronic Transactions) Faculty of Law, Islamic University As-Syafi’iyah, 2020. This thesis discusses the theft of personal data that often occurs but law enforcement is still minimal. The object of research uses a case study of the Purwakarta District Court Decision with the problem approach used is the normative juridical problem approach, namely the approach taken through literature study by examining secondary data in the form of laws and regulations, and empirical juridical by conducting interviews with several sources of regulation analysis and analysis law enforcement process. Lack of awareness of the victims to report their cases, makes the law enforcement process is still minimal. Based on the results of the research and discussion carried out that in law enforcement against the theft of personal data of the user of the provider is carried out by means of prosecution and non-punishment by the Purwakarta Regional Police and the Ministry of Communication and Information.